Taipei,China's Banking Problems: Lessons from the Japanese Experience - Heather Montgomery (Asian Development Bank Institute (ADBI), 2002)
The economy of Taipei,China was able to escape the contagion of the Asian financial crisis and remains well insulated from the type of external shocks that forced other economies in the region into currency devaluations and deep recession in 1997. Since that time however, internal pressures have gradually weakened many of Taipeis banks and now threaten the stability of the banking sector as a whole. The domestic nature of these pressures have led to comparisons with the experience of Japan in the 1990s. Early warning signs of the banking sector problems in Taipei,China have been evident since the mid-1990s in the form of falling ROA and ROE ratios, steadily rising non-performing loans and bank runs at several small financial institutions. More recently, the takeover of two medium-sized banks by the financial reconstruction fund has brought to light the fact that the problems have spread beyond the small credit cooperatives and credit departments of farmers and fishermens associations. The experiences of Taipei,China thus far closely resemble the early stages of Japans banking sector problems. Since 1990, Japans banking sector has also demonstrated declining ROE and ROA ratios. Non-performing loans have been an issue since the early 1990s as well, and as in Taipei,China, non-performing loan ratios have always been particularly acute in Japans smaller financial institutions. In fact, several credit cooperatives and shinkin banks were closed in the 1990s. Often, these failures were resolved via the convoy system under which weak financial institutions are taken over by larger, stronger banks, a practice which has been adopted by authorities in Taipei,China as well. In Japan, the banking sector problems finally erupted into a full-blown banking crisis in 1997, with the collapse of three of the top 20 banks that had previously been considered too big to fail. There are similarities in not only the symptoms, but also the causes of the banking sector problems in Taipei,China and Japan. In both cases, macroeconomic shocks, in particular the asset bubbles in equity and real estate prices, played a significant role in weakening the banking sector. But the crucial factor in both cases was the combination of these macroeconomic shocks with financial deregulation, which led to disintermediation and over-banking in the financial sector. As documented here, policy makers in both Taipei,China and Japan, have taken steps to address the weakness of the banking system in each economy. While acknowledging the aggressive response of policy makers in Taipei,China, this study points out that there are many lessons positive and negative to be learned from the experience of Japan. In particular, policy makers in Taipei,China are urged to heed the early warning signs of overall banking sector problems and to avoid the policy of forbearance. Macroeconomic recovery cannot be relied upon to help banks grow out of their problems.
hdl:11540/4148
Keywords: 330